Muscarinic receptor binding increases in anterior thalamus and cingulate cortex during discriminative avoidance learning - Vogt, BA (J Neurosci, 1991)
Training-induced neuronal activity develops in the mammalian limbic system during discriminative avoidance conditioning. This study explores behaviorally relevant changes in muscarinic ACh receptor binding in 52 rabbits that were trained to one of five stages of conditioned response acquisition. Sixteen naive and 10 animals yoked to criterion performance served as control cases. Upon reaching a particular stage of training, the brains were removed and autoradiographically assayed for 3H-oxotremorine-M binding with 50 nM pirenzepine (OXO-M/PZ) or for 3H-pirenzepine binding in nine limbic thalamic nuclei and cingulate cortex. Specific OXO-M/PZ binding increased in the parvocellular division of the anterodorsal nucleus early in training when the animals were first exposed to pairing of the conditional and unconditional stimuli. Elevated binding in this nucleus was maintained throughout subsequent training. In the parvocellular division of the anteroventral nucleus (AVp), OXO-M/PZ binding progressively increased throughout training, reached a peak at the criterion stage of performance, and returned to control values during extinction sessions. Peak OXO-M/PZ binding in AVp was significantly elevated over that for cases yoked to criterion performance. In the magnocellular division of the anteroventral nucleus (AVm), OXO-M/PZ binding was elevated only during criterion performance of the task, and it was unaltered in any other limbic thalamic nuclei. Specific OXO-M/PZ binding was also elevated in most layers in rostral area 29c when subjects first performed a significant behavioral discrimination. Training-induced alterations in OXO-M/PZ binding in AVp and layer Ia of area 29c were similar and highly correlated.